Self-organized TiO2 nanotube layer on Ti–6Al–7Nb for biomedical application - Rafieerad, A.R.; Zalnezhad, E.; Bushroa, A.R.; Hamouda, A.M.S.; Sarraf, M.; Nasiri-Tabrizi, B. (Elsevier, 2015)
In the present study, a self-organized nanotube TiO2 layer on Ti-6Al-7Nb was fabricated. The influence of acidic electrolytes including glycerol (G) and ethylene glycol (EG) on the anodization, microstructural features and surface wettability was explored. The phase compositions and morphological characteristics were characterized by X-ray diffraction (XRD) and field emission scanning electron microscopy (FE-SEM), respectively. According to the results, due to the intrinsic amorphous feature of ceramic oxide, the characteristic TiO2 peaks were not detected in the XRD profiles. After annealing in normal atmosphere at 600 degrees C for 2 h, TiO2 crystallized and consequently, nanotubular TiO2 arrays containing anatase and rutile phases formed. From a microstructural point of view, the average length and diameter of the nanotube array ranged from 2.23 to 4.22 mu m and 160 to 170 nm, respectively. Besides, the type of acidic electrolyte and subsequent annealing noticeably affected the surface wettability of the products. (C) 2015 Elsevier B.V. All rights reserved.